S37 Home mechanical ventilation (hmv) and home oxygen therapy (hot) following an acute exacerbation of copd in patients with persistent hypercapnia: results of the per protocol analysis from the hot-hmv uk trial. (15th November 2017) - Murphy, PB; Arbane, G; Phillips, R; Hart, N
Abstract : Introduction: Intention-to-treat analysis from the HOT-HMV UK trial showed an improvement in admission-free survival with the addition of home mechanical ventilation (HMV) to home oxygen therapy (HOT) in patients with persistent hypercapnia following an acute exacerbation of COPD [JAMA;317:2177]. Delivery of HMV is essential and a per-protocol analysis was conducted to assess if patients who were adherent had better outcome. Method: Patients were randomised to HOT or HOT-HMV if they had persistent hypercapnia (PaCO2 >7 kPa) 2 weeks following resolution of respiratory acidosis (pH >7.30) secondary to an acute exacerbation of COPD. NIV was titrated to nocturnal hypoventilation and patients were followed up for 1 year. Patients allocated to the HOT arm that breached safety criteria had HMV added to HOT. Patients were included in the analysis in the HOT-HMV group if they had mean adherence of >4 hours/night. Patients allocated to HOT were included up until trial withdrawal or treatment switching. Results: 57 patients were randomised to HOT-HMV of whom 15 were non-adherent and 11 had missing usage data and were treated as non-adherent. 59 patients were allocated to HOT of whom 5 patients were excluded due to treatment switching. Median time to readmission or death was 1.1 months in the HOT group and 3.7 months in the HOT-HMV group (adjusted hazard ratio (HR) 0.41, 95% CI 0.23, 0.74, p=<0.01). All-cause mortality was reduced in the HOT-HMV group (figure 1 ; adjusted HR 0.36, 95% CI 0.13, 0.97, p=0.04). There was a significant treatment effect on PaCO2 at 6 weeks (ΔpCO2 −0.9 kPa, p<0.01) which was observed at 12 months (pCO2 −0.7 kPa, p=0.04) with no significant effect on health related quality of life at 6 weeks (SRI p=0.28, SGRQ p=0.98) or 12 months (SRI p=0.71, SGRQ p=0.31). Conclusion: Patients with persistent hypercapnia following an acute exacerbation of COPD who were adherent to HOT-HMV had a reduced risk of readmission or death and in addition, unlike the intention to treat analysis, had an improvement in gas exchange and a reduction in all-cause mortality at 12 months. Addition of HMV to HOT should be considered for patients with persistent hypercapnia following a life-threatening exacerbation of COPD.